2022
DOI: 10.3389/fphar.2021.795483
|View full text |Cite
|
Sign up to set email alerts
|

Polydextrose Alleviates Adipose Tissue Inflammation and Modulates the Gut Microbiota in High-Fat Diet-Fed Mice

Abstract: The soluble dietary fiber polydextrose (PDX) is a randomly linked glucose oligomer containing small amounts of sorbitol and citric acid and is widely used in the food industry. However, whether PDX can prevent and treat obesity in high-fat diet (HFD)-fed mice has not been directly investigated, and further studies are needed to better understand the complex interactions among PDX, adipose tissue inflammation and the gut microbiota. In the present study, PDX reduced body weight, fasting blood glucose (FBG), adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 57 publications
2
13
0
Order By: Relevance
“…Prevotellaceae_UCG-001 also produces SCFAs, which stimulates glucagon secretion and increases satiety to regulate fat synthesis and cholesterol in the liver and inhibit weight gain ( Maljaars et al, 2008 ; Wang M. et al, 2019 ). Previous studies had shown that high-fat diet–induced obese mice had a higher abundance of GCA-900066575 than wild mice ( Li et al, 2020 ; Hu Q. et al, 2021 ). However, we found that the abundance of GCA-900066575 increased in the H-TF3 group rather than in ob/ob obese mice.…”
Section: Discussionmentioning
confidence: 94%
“…Prevotellaceae_UCG-001 also produces SCFAs, which stimulates glucagon secretion and increases satiety to regulate fat synthesis and cholesterol in the liver and inhibit weight gain ( Maljaars et al, 2008 ; Wang M. et al, 2019 ). Previous studies had shown that high-fat diet–induced obese mice had a higher abundance of GCA-900066575 than wild mice ( Li et al, 2020 ; Hu Q. et al, 2021 ). However, we found that the abundance of GCA-900066575 increased in the H-TF3 group rather than in ob/ob obese mice.…”
Section: Discussionmentioning
confidence: 94%
“…Coprostanoligenes is a central fecal microbial group for individuals on HFD, mainly through sphingosine to mediate blood lipid metabolism ( 60 ). Ruminococcaceae UCG-014 , Ruminiclostridium 1 , and Allobaculum are SCFA-producing microbiota and play important roles in maintaining a healthy gastrointestinal tract ( 61 63 ), improving NASH ( 64 ), and alleviating adipose tissue inflammation ( 65 ). Consistent with other studies ( 66 , 67 ), HFD-fed mice had fewer Ruminococcaceae UCG-014, Ruminiclostridium 1 , and Allobaculum than the NFD group, while L. plantarum ZJUIDS14 treatment reversed their relative abundance in the colon of HFD-fed mice.…”
Section: Discussionmentioning
confidence: 99%
“…The results achieved in the present study agree with those previously reported by other authors. Thus, a study exploring adipose tissue inflammation and gut microbiota interactions revealed that the administration of Polydextrose to obese mice (fed a high-fat diet) promoted the growth of microbes including Ruminococcaceae UCG-014 and UBA-1819 , and that all of them were negatively correlated with body weight and fat content, glucose, and inflammation markers [ 51 ]. The involvement of further mechanisms underlying the effects of resveratrol intake cannot be discarded.…”
Section: Discussionmentioning
confidence: 99%